2017
DOI: 10.1002/mrm.26921
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous mechanical and electrical activities of human calf musculature at rest assessed by repetitive single‐shot diffusion‐weighted MRI and simultaneous surface electromyography

Abstract: Visible SMAMs in DWI have shown a close and direct relation to concurrent signals recorded by sEMG. MR-related magnetic fields had no significant effects on findings in sEMG. Hence, appearance of SMAMs in DWI should not be considered as imaging artifact or as effects originating from the special conditions of MR examinations. Spatial and temporal distributions of SMAMs indicate characteristics of spontaneous (microscopic) mechanical muscular action at rest. Therefore, DWI techniques should be considered as non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…In another recent study, possible correlations between DWI and EMG on healthy volunteers could be identified (Surov et al., ). It was shown that spontaneous muscle activity can be detected on DWI and surface EMG in a similar fashion, and therefore this study is in good agreement with the present study that both modalities are linked to each other (Schwartz et al, ). We hereby present the first data regarding possible associations between ADC and EMG.…”
Section: Discussionsupporting
confidence: 93%
“…In another recent study, possible correlations between DWI and EMG on healthy volunteers could be identified (Surov et al., ). It was shown that spontaneous muscle activity can be detected on DWI and surface EMG in a similar fashion, and therefore this study is in good agreement with the present study that both modalities are linked to each other (Schwartz et al, ). We hereby present the first data regarding possible associations between ADC and EMG.…”
Section: Discussionsupporting
confidence: 93%
“…This is remarkably similar to published estimates of human motor unit diameter based on scanning electromyography . Further studies have shown that these voids are usually preceded by electrical activity recorded using surface electromyography but have not determined the anatomical substrate in which they are generated . We hypothesized that the signal dropout was caused by the bulk movement of water resulting from the contraction of individual motor units rather than simple diffusion.…”
Section: Patient Id Age Yr Time Since Diagnosis Mo Als Classificatisupporting
confidence: 80%
“…In a recent study, a strong correlation between visible SMAMs in DWI and electrical activities measured by surface electromyography at the skin surface was revealed. These findings provide evidence that SMAMs are related not only to undesired artifacts in diffusion‐weighted MRI, but also to spontaneous muscular activity potentially relevant to other fields of muscular research . Each SMAM in resting skeletal musculature seems to be a unique event related to a random spatial and temporal movement pattern visible in DWI .…”
Section: Introductionmentioning
confidence: 66%
“…Since SMAMs visible in DWI first are strongly correlated to preceding surface electromyography measurable electrical activities, second are assumed to be not caused by MR gradient switching and third have shown a distinct connection to anatomical characteristics such as fiber orientation, SMAMs seem to be clearly related to physiological muscular processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation